Study of Sasaknese Proverb and Its Significances in Social life: Semiotics Rolland Barth Analysis - Syamsurrijal Syamsurrijal; Zainudin Abdussamad; Abdul Muhid (LPPM Universitas Bumigora Mataram, 2023)
Sasak ethnic is people who occupied Lombok Island. Sasak ethnic has uniqueness in expressing their thought and feeling so called sêsênggak. Sêsênggak is the expression sasakness feeling and thought which have intrinsic and extrinsic meaning. The expression used local language as result many Sasaknese especially youth not fully comprehend the real meaning of proverb. Therefore, the current research conducted research based on Rolland Barthe theory in order give insight and knowledge to youth dealing with message behind the proverb. The objective of the research is to reveal the meaning of denotation, connotation and in its significances to the Sasak ethnic of Lombok Island, West Nusa Tenggara. This research employed qualitative descriptive in which the data taken from book, document and internet. Based on the results of the data analysis, several things can be concluded. First, the connotative meanings in sêsênggak are descriptions of the basic representations of mental capacities that Sasak people used in the past to conceptualise themselves and their world. Second, based on the meanings found, sêsênggak has the function of expressing thoughts that contain general truths that serve to control and judge individual or group attitudes/behaviours. Third, the myth shows that sêsênggak carries messages of morality, education, law, wisdom, economic and social values, and the like. Therefore, sêsênggak cannot be separated from the normative and evaluative description of an attitude or behaviour of the speaking community in a limited context and the general public in a wider context.